Aggressive low grade middle ear adenocarcinoma with multiple recurrences: a case report - Elhefnawy Nadia G (BMC, 2011)
Abstract Background Primary tumours of the middle ear are much less commonly encountered in clinical practice than non neoplastic lesions. Middle ear adenocarcinoma is a very rare, locally invasive neoplasm assumed to arise from the middle ear mucosa. Because the natural course and clinical behavior of this neoplasm are far from established, the sporadic reports of such cases continue to provide basis for better understanding. Case description A case of low grade adenocarcinoma of the middle ear is described in details with regard to its clinical presentation, radiological findings, histopathological, immunohistochemical and ultrastructural findings. The tumour recurred four times.